2002
DOI: 10.1103/physrevc.65.054611
|View full text |Cite
|
Sign up to set email alerts
|

Barrier distributions in16O+116,119Snq

Abstract: Using the Warsaw cyclotron beam we have determined barrier distributions from the quasielastic scattering of 16 O on 116,119 Sn targets. They turned out to be similar in both systems. To improve the signal/noise ratio, digital filters were applied in the data analysis procedure and are discussed in detail. Experimental results were compared with coupled-channels calculations performed using the FRESCO code. Reasonable agreement between experiment and theory was obtained but some disagreements remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…4 to Fig. 6 [4,5,34,38,39,40] are also presented for comparison. The solid circles and squares denote the measured fusion cross sections σ fus and large-angle quasi-elastic scattering cross sections, respectively.…”
Section: B Description Of Large-angle Quasi-elastic Scatteringmentioning
confidence: 99%
“…4 to Fig. 6 [4,5,34,38,39,40] are also presented for comparison. The solid circles and squares denote the measured fusion cross sections σ fus and large-angle quasi-elastic scattering cross sections, respectively.…”
Section: B Description Of Large-angle Quasi-elastic Scatteringmentioning
confidence: 99%
“…However, a systematic study on barrier distribution measured from fusion cross sections using 12 C, 16 O, 28 Si, and 35 Cl on 92 Zr [4] and comparison with the exact coupled-channels code CCFULL [8] without transfer channel coupling, suggested that the barrier distribution shape could have been reproduced better by including positive Q-value transfer channels present in the case of 28 Si-and 35 Clinduced reactions. The enhancement in subbarrier fusion cross sections because of positive Q-value neutron transfer channels has been studied for 16,17 O+ 144 Sm [9], 32,36 S+ 110 Pd [10], 40 Ca+ 90,96 Zr [11], 40 Ca+ 46,48,50 Ti [12], and 16,18 O+ 120,124 Sn [13] systems. The fusion barrier distributions for 32,34 S+ 89 Y systems extracted from the measured fusion cross sections were explained by including the collectivity of the projectiles.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion cross section (σ fus ) for the heavy ion reaction under the adiabatic and isocentrifugal approximation can be written as a weighted sum of the fusion cross sections for a number of eigenchannels which depend on the direct reaction channel and couple strongly to the incident one [16,17]:…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the excitation function of the cross sections at θ = π for the 16 (10). The dotted line shows the reflection probability R(E) = |S(E)| 2 .…”
Section: B Quasi-elastic Test Functionmentioning
confidence: 99%
“…The last point not only improves the efficiency of the experiment, but also allows the use of a cyclotron accelerator where the relatively small energy steps required for barrier distribution experiments cannot be obtained from the machine itself. This fact was recently exploited by Piasecki et al [10], who took an astute choice of the scattering angles at which σ qel was measured in order to have the energy range necessary, while retaining relatively small energy steps. Moreover, these advantages all point to greater ease of measurement with low-intensity exotic beams.…”
Section: Introductionmentioning
confidence: 99%